Evaluation of Perioperative Pain Treatment of Tonsillectomy Patients Using Prospect Recommendations in Tertiary Hospitals - Gul e Nazish, Arshadullah Afridi, Asma Inam, Maniha Sanawar, Mahreen Akhtar, Waleed Arshad, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Tonsillectomy is a painful surgical procedure accompanied by moderate to severe pain several days after surgery. Despite the often severe pain after tonsillectomy, under-treatment of pain has been consistently reported. The cause of this under-treatment is inadequate education of health care professionals regarding pain management. Objectives: The aim of this study was to assess perioperative pain treatment given to tonsillectomy patients in otorhinolaryngology departments of tertiary care Hospitals using Procedure specific post-operative pain management (PROSPECT) guidelines for tonsillectomy. Methodology: It was an observational study with prospective data inclusion. A questionnaire was designed and filled by investigators on three different occasions (pre-operative, intra-operative and post-operative). Questionaire was comprised of Patient’s demographic details, surgical indication, surgical technique used, post-operative complications and details of analgesics used during pre-operative, intra-operative and post-operative settings. Results: NSAIDs (Ibuprofen, ketorolac, Flurbiprofen) were predominantly used class for perioperative analgesia alone or in combination with each other among tonsillectomy patients. Dexamethasone injection was given intra-operatively to 97% of the patient regardless of age. Nelbuphin an opioid analgesic was used only in 7% of the patients intra-operatively. Conclusion: Current study indicates that perioperative pain management for tonsillectomy in two tertiary care hospitals of Punjab was in conformity with PROSPECT guidelines for tonsillectomy patients. Patients were given standard pain treatment. However, study needs a further evaluation with larger data from different hospitals. Keywords: PROSPECT, Analgesic, Tonsillectomy, NSAIDS, Opioids